Lead Content on Fried Foods Against Seller Sanitation and Fried Frequency in the Area of Semarang City - Mutiara Afri Sagita; Nikie Astorina Yunita Dewanti; Sulistiyani Sulistiyani (Universitas Airlangga, 2020)
Introduction: Fried food is a snacks that is widely consumed and become a favorite food of Indonesian society, the food is usually consumed more than once in a single meal. However fried foods are also foods that are easily contaminated physically, microbiological and chemical. Preliminary study results indicate the presence of unqualified lead levels in fried foods. In the meantime, it has a toxic effect on the body that is mutagen, teratogen and carcinogen. This research aims to analyze the sanitation condition of sellers with a lead content on fried food in the subdistrict of Pedurungan Semarang. Method: This research was an analytical observational research with a cross sectional design study. Determination of the sample by the total sampling method of 38 fried food merchants and Bakwan fried samples. Data analysis was performed using a correlation test Rank Spearman. This research had been worthy of ethics through the commission of Ethics of Health Research Faculty of Public Health of Diponegoro University with number 285/EA/KEPK-FKM/2019. Result and Discussion: The lead rate of the average fried meal was 0.184 mg/kg and the fried frequency was 24 times in a moment. The results of a correlation analysis of Rank Spearman showed no significant link between the serving Mat material (p value = 0.008), the sanitary condition of snacks facilities (p value = 0.011) and the fried frequency (p value = 0.001) with a lead content in fried foods. Conclusion: The sanitation factor of the seller's facilities related to the lead content in the Sub-district of Pedurungan is the presentation base material, sanitary conditions and fried frequency.